Palm oil (Elaeis Guineensis) based substance for the production of nontoxic oil paint for artist / Muhammad Sophist Ahmad - Ahmad, Muhammad Sophist (Institute of Graduate Studies, UiTM, 2013)
Thesis entitled Palm Oil (Elaeis guineensis) based Substance for the Production of Nontoxic Oil Paint for Artist is a cluster-based academic research in the social sciences highlighted innovative elements generated through trans studies approach that involves collaboration between two faculties: the Faculty of Art and Design (FAD) and the Faculty of Chemical Engineering (FCE), Universiti Teknologi MARA (UiTM), Malaysia. Intents to cooperate with the FCE, UiTM is to achieve the alpha prototypes of nontoxic oil paints as the alternative locally-made nontoxic painting mediums for application on canvas to be used by local artists amongst the lecturers, students, and full-time oil painters that come from the fine art majors. Based on trans studies approach, the researcher is responsible to develop the prototypes of alpha rather than beta. In other words, alpha refers to the first prototype version to run, while beta is a pre-production on nearly ready-to-market products based on the alpha baseline. The researcher upholds the alpha prototypes to serve as an initial platform or a baseline for a reference to any future researchers to bring the alpha prototypes of nontoxic oil paints to reach the beta stages in the future commercialisation…